THE EFFECT OF STORE ATMOSPHERE ON PERCEIVED SERVİCE QUALITY: A RESEARCH ON LARGE SCALE RETAIL STORE (Third Sector Social Economic Review, 2018)
In today's marketing understanding, enterprises touch to the to the emotional worlds of consumers and aim to leave emotional effects and quality perception on consumers on the purpose of gaining competitive advantages against their competitors. In order to achieve these goals, enterprises are increasingly paying more and more attention to the atmosphere of the stores, which is one of the points of contact with consumers. In this respect, the main aim of this study is to examine the effect of store atmosphere on the quality of service that is perceived by the customers. Being able to present this effect, which is extremely important in terms of increasing customer satisfaction, can provide important inputs for enterprises that aim to gain competitive advantage in the market. This study was designed within the scope of the IKEA store in Ankara. The data obtained through questionnaire from IKEA customers living in Ankara were analyzed by evaluating statistically the effect of atmosphere on perceived service quality.
Keywords: Store Atmosphere; Perceived Service Quality; Customer Satisfaction; Retailing